The Antitumoral Effect of Paris Saponin II on Head and Neck Squamous Cell Carcinomas Mediated via the Nitric Oxide Metabolic Pathway - Qi, Wenwen; Zhu, Fangyuan; Wang, Min; Teng, Zhenxiao; Xu, Runtong; Xi, Yue; Meng, Qiu; Wu, Xinhao; Zhao, Hui; Ma, Min; Hou, Xiaozhi; Wang, Baowei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Paris saponin has shown great therapeutic value in cancer therapy. We used isolated Paris saponin II (PSII), an active component of Paris saponin, and demonstrated its antitumor effect on human head and neck squamous cell carcinoma cell lines. Additionally, we investigated its mechanisms of action in vivo by establishing a xenograft mouse model. The results showed that PSII had presented strong anticancer effects on both hypopharyngeal malignant tumor cell lines (FaDu) and laryngeal carcinoma cell lines (Tu212 and Tu686). In addition, we successfully isolated and cultured the head and neck squamous stem cells and the primary fibroblasts to perform metabonomics studies. The results showed that RPII remarkably decreased energy metabolism, and type III nitric oxide synthase 3 (NOS3) may be a target to block tumor growth. Furthermore, we found that PSII inhibited HNSCC proliferation and metastasis by inhibiting the nitric oxide metabolic pathway. Overall, these results demonstrated that PSII is a potent anticancer agent, and the metabonomics analysis is a valuable tool to investigate and establish the antitumor effects of traditional Chinese medicines.